Metastasic Liposarcoma in abdomen. On purpose of a case - Belkis Magdalena Martínez Martínez; Tania Milagros Suárez Núñez; Ilse Busto Vales (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction:The liposarcoma is a wicked tumor of origin derived mesodermic of the fatty fabric, it is the most frequent in the adult's sarcomas and the abdominal localization is strange, ending up reaching enormous proportions. Objetive: To present the case of a patient with liposarcoma pleomorfo stage IV, of abdominal localization. Presentation of the case:Woman 42 year-old patient, quarter note that she goes for increase of volume and diffuse pain of the abdomen of a month of evolution. The initial diagnosis was gynecological Neoplasia with peritoneal infiltration, with a torpid evolution. The anatomo-pathological conclusion was a Liposarcoma Pleomórfico in stage IV. The decision of presenting this case, it is based in the first place by the patient's age, the uncommon but very aggressive variety of this tumor and the fatal outcome that this had. Conclusions: The reflective presented patient a due late diagnosis fundamentally to the anatomical localization that conditioned the growth tumoral without it was suspected until an advanced stage in stadium IV. The variety very aggressive histological, for its high degree of malignancy and great metastasis incidence, contributed causing the peritoneal infiltration negatively, of the organs of the pelvic floor and finally the death. Keywords: Liposarcoma, Pleomorfic, Desdiferenciado, Mixoide (round cells), Neoplasia, fatty fabric, metastasic.